Considerations on psychophysical welfare of fish employed in scientific procedures and on Recommendation 2007/526/EC - Arianna Manciocco; Paolo Coluccio; Annamaria Passantino (Istituto Superiore di Sanità, 2010)
The use of fish for experimental purposes has seen a significant increase over the past years, consequently scientific findings on factors influencing welfare of these vertebrates are now available, as well as debates on their capacity of experiencing suffering are increasingly found in animal welfare discussions. Nowadays, in Europe, the use of these animals as experimental models is regulated by the Recommendation 2007/526/EC, where in the Section on the species-specific guidelines for fish, aspects such as the environmental characteristics of housing, the monitoring of animal health, the general care of subjects (i.e. feeding, handling, transport), and the killing procedures, are considered. In this manuscript, some aspects regarding the use of fish for human benefits will be discussed, and the suggestions provided by the European legislation are pointed out in order to identify limits and advantages.